THE LEGAL FRAMEWORKS FOR INSTITUTIONAL REFORM AND THEIR IMPACT ON PROMOTING TRANSITIONAL JUSTICE: THE POST-2003 IRAQI EXPERIENCE AS A CASE STUDY - Yassin Jassim Mohammed; Fares Mohammed Hussein (International Journal of Business, Law and Political Science, 2026)
Objective: This research aims to shed light on the pivotal role of "Institutional Reform" as a fundamental pillar and a core guarantee for the non-recurrence of violations within transitional justice processes. Method: To achieve its objectives, the study employs descriptive, analytical, and comparative methodologies by analyzing the experiences of Tunisia and Iraq as models of political transition 2003, respectively. Results: The research has reached several key findings, most notably that the success of institutional reform is directly proportional to the independence of national decision-making and the capacity for individual professional vetting of employees, rather than collective exclusion policies that may lead to security and administrative vacuums. Furthermore the study confirms that rebuilding citizen trust in state institutions is the true indicator of the success of transitional justice and the legitimacy of the new political system. Novelty: The study stems from a primary problem centered on the effectiveness of international and national legal frameworks in transforming state institutions from oppressive tools into democratic structures that uphold the rule of law.